THE EFFECT OF AGILITY TRAINING ON BASKETBALL JUMP PASS ABILITY IN STATE HIGH SCHOOL 2 STUDENTS FUCK SEI TUAN: PENGARUH LATIHAN KELINCAHAN TERHADAP KEMAMPUAN JUMP PASS BOLA BASKET PADA SISWA SMA NEGERI 2 PERCUT SEI TUAN - Ibnu Tryaghnansyah (LPPM UPMI, 2023)
The type of research used is experimental. According to Sugiyono (2010:7) explains that research with an experimental approach is research that tries to find the influence of certain variables on other variables under strictly controlled conditions. The population in this study were 12 students at SMA Negeri 2 Percut Sei Tuan. The sampling technique used was total sampling, namely 12 students at SMA Negeri 2 Percut Sei Tuan. In connection with several terms used in this research, to emphasize the terms used, and to avoid misinterpretation regarding the title of the research, as well as to obtain a clear picture that leads to the research objectives, it is necessary to emphasize the terms used in the research . These results will be tested at a significance level of 5% or a confidence level of 95%. The results of the research show that after participating in the agility training program, the students' jump pass ability significantly increased. This can be seen from the comparison of statistics before and after the training program. The average value of jump pass ability increased significantly, and this difference was proven to be significant based on the statistical analysis carried out. Agility training was in the poor category with 4 students (23.3%), the sufficient category with 26 students (34.2%), the good category with 0 students (0%) and the very good category with 0 students (0%). In the observation of Jump Pass Basketball, 4 students (23.3%) were in the poor category, 26 students (33.5%) in the fair category, 0 students (0%) in the good category and 0 students (0%) in the very good category. In this research, students of SMA Negeri 2 Percut Sei Tuan